A participação e representação política das mulheres nas comissões executivas do PP e PT no município de Santa Maria/RS - Silva, Gabriela Machado Da (2019)
The female presence in various sectors of our society has been marked by its gradual insertion in leadership positions. However, their exclusion in the spheres of power over political decisions and, more specifically, the central nuclei of power of party life still persist. The low political inclusion of Brazilian women in decision-making spaces led to debates, conflicts and, subsequently, legislation aimed at ensuring participation and representation in the authorities; and transform that reality. However, the quota law (2010), which provides, among other measures, that a minimum of 30% of applications must be filled for each gender, has not been able to generate gender balance in the legislature. Among the factors pointed to as possible causes of the low female political presence are the non-compliance of the parties, with false candidacies or candidacies without any party adhesion, inequalities in campaign financing, little incentive within the parties for their participation and inferior political capital. Since within the party organization executive committees have the competence to make decisions in general, this space becomes a priority for the insertion of women. This research is characterized, through a mixed approach (qualitative quantitative), of descriptive and explanatory type, which seeks through a comparative study, to analyze the participation and political representation of women and also to identify the insertion of women in decision-making spaces. of the above parties. Comparative analyzes will be operationalized, with regard to political participation, as a dimension of legality and gender parity and political representation, while the dimension of symbolic and key positions in order to identify the spaces and roles occupied by these women.